Genes, chromosomes, and disease : from simple traits, to complex traits, to personalized medicine - Gillham, Nicholas W. (New Jersey : FT Press Science, 2011)
Annotation. This overview covers the rise of medical genetics through the past century and the eugenic impulses it has inspired. It reviews the linkages between genes and disease, ethnic groups' differential susceptibility to genetic traits and disorders, personalized medicine and crucial social and ethical issues arising from progress.
Hunting for disease genes -- How genetic diseases arise -- Ethnicity and genetic disease -- Susceptibility genes and risk factors -- Genes and cancer -- Genes and behavior -- Genes and IQ : an unfinished story -- Preventing genetic disease -- Treating genetic disease -- The dawn of personalized medicine.
Includes bibliographical references (pages 253-291) and index.
Keywords: Genetic disorders -- Susceptibility; Human chromosomes; Genetic Diseases, Inborn -- genetics; Chromosomes, Human; Genetic Diseases, Inborn -- therapy; Genetic Predisposition to Disease -- genetics; Genetic Techniques